Pengaruh Biaya Bahan Kimia Dan Biaya Energi Terhadap Kinerja Bidang Keuangan (Studi Kasus Pada Perusahaan Daerah Air Minum Se-Jawa Timur Tahun 2015-2018) - Darno Darno; Retno Nur Cahyani (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
The purpose of this study is to understand the effect of chemical costs and energy costs on the financial performance of PDAMs in East Java. The object of this research is the Regional Drinking Water Company in East Java with a time span of 2015 – 2018. This research uses descriptive quantitative method. The population in this study were 38 regional drinking water companies in East Java. The sample contained in this study used the purposive sampling technique. This research was processed using multiple linear regression analysis. The results of the study explain that the t-test (partial) on the cost of chemicals is 0.433, while the cost of energy is -1.890. Based on the results of the F test (simultaneous) it shows a value of 1.788 which means that there is no simultaneous influence between the independent variables, namely the cost of chemicals and energy costs, on the dependent variable, namely the performance of the financial sector.